2007
DOI: 10.1111/j.1423-0410.2007.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory variation in the detection of HPA‐specific alloantibodies and in molecular HPA typing

Abstract: The ability to detect and to identify platelet-specific alloantibodies varied widely between laboratories and between various examples of antibodies issued. An increase in the number of laboratories screening for HPA-15 antibodies was seen, although detection and identification of these antibodies was problematic. The majority of examples of HPA-3a antibodies and some examples of HPA-1a and -5b were also difficult to detect and identify. In addition, this scheme has shown that despite the apparent reliability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
0
22
0
2
Order By: Relevance
“…We previously showed that particular capture mAbs were associated with nondetection of some examples of anti-HPA-1a [17]. This current exercise showed that reduced assay sensitivity occurred with all nine clones used.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We previously showed that particular capture mAbs were associated with nondetection of some examples of anti-HPA-1a [17]. This current exercise showed that reduced assay sensitivity occurred with all nine clones used.…”
Section: Discussionmentioning
confidence: 76%
“…However, detection and identification of such antibodies remains problematic [12,14,17]. We recently reported decreased sensitivity of assays for HPA-1a antibodies resulting from dissociation of integrin aIIbb3 by the cation-chelating compound, EDTA, often used in buffer solutions, as the anticoagulant for samples from which platelets are extracted, or in test samples [10].…”
Section: Discussionmentioning
confidence: 97%
“…Initially, in the first phase, 51 well‐characterized blinded samples were used to familiarize the participating laboratories with the bead assay technique, to resolve interlaboratory experimental differences, and to generate a training set of results for use in a gating algorithm to classify samples in the second phase of the study. The reactivity of these 51 samples had been previously defined by the results of several large international QA scheme exercises with more than 30 participating laboratories . The composition of the training set of 51 QA samples reflected what is commonly encountered in the clinical setting with antibodies against HPA‐1a being the main cause of FMAIT…”
Section: Discussionmentioning
confidence: 99%
“…Elle varie également en fonction du niveau d'expression des antigènes HPA-15 sur la membrane plaquettaire. L'évaluation interlaboratoire régulière d'échantillons sériques ou plasmatiques confirme la difficulté persistante de la détection des Ac anti-HPA-15 [12]. Ainsi, le nombre de laboratoires participants utilisant un Ac anti-CD109 dans le test de MAIPA a significativement augmenté, passant de 0 % en 1996 à 89,5 % en 2006.…”
Section: Discussionunclassified